On the structure of the present-day convergence. Issue 2 (25th February 2014) - Korotayev, Andrey; Zinkina, Julia
Abstract : Purpose: – A substantial number of researchers have investigated the global economic dynamics of this time to disprove unconditional convergence and refute its very idea, stating the phenomenon of conditional convergence instead. However, most respective papers limit their investigation period with the early or mid-2000s. In the authors' opinion, some of the global trends which revealed themselves particularly clearly in the second half of the 2000s call for a revision of the convergence issue. The paper aims to discuss these issues. Design/methodology/approach: – Several methodologies for measuring the global convergence/divergence trends exist in the economic literature. This paper seeks to contribute to the existing literature on unconditional β -convergence of the per capita incomes at the global level. Findings: – In the recent years, the gap between high-income and middle-income countries is decreasing especially rapidly. The gap between high-income and low-income countries, meanwhile, is decreasing at a much slower pace. At the same time, the gap between middle-income and low-income countries is actually widening. Indeed, in the early 1980s GDP per capita in the low-income countries was on average three times lower than in the middle-income countries, and this gap was totally overshadowed by the more than ten-time abyss between the middle-income and the high-income countries. Now, however, the GDP per capita in low-income countries lags behind the middle-income ones by more than five times, which is largely the same as the gap (rapidly contracting in the recent years) between the high-income and the middle-income countries. This clearly suggests that the configuration of the world system has experienced a very significant transformation in the recent 30 years. Research limitations/implications: – The research concentrates upon the dynamics of the gap in per capita income between the high-income, the middle-income, and the low-income countries. Originality/value: – This paper's originality/value lies in drawing attention to the specific changes in the structure of global convergence/divergence patterns and their implications for the low-income countries.